Stem demography and post fire recruitment of Podocarpus drouynianus: a resprouting non-serotinous conifer - Chalwell, S.T.S; Ladd, P.G (Botanical journal of the Linnean Society, 2005)
Podocarpus drouynianus is unusual in the Podocarpaceae and conifers in general in being a strongly resprouting species which thrives in a fire‐prone environment. The species is a dioecious, multi‐stemmed shrub endemic to the eucalypt forests of the south‐west of Western Australia. Stems are killed by fire but it is able to regenerate its foliage from a lignotuber. The total bud bank seems to be released by burning and death of the shoots, while pruning without fire releases only a proportion of available buds. Growth rate of resprouts is initially rapid, with stems reaching 25% of their mature length in the first year after fire. However, growth of juvenile plants is very slow. Fire promotes cone production on the new stems about one year after fire. The large seed is recalcitrant but timing of germination coincides with the wettest time of the year in the area where the species grows. Pyrogenic coning avoids loss of seed due to severe fires and is a form of mast reproduction that benefits this species by increasing pollen transfer and producing a mass seed crop to attract the primary vertebrate disperser – the emu. The strong resprouting ability ensures the species is resilient to frequent disturbance and to severe predation of the seed crop. Vertebrate dispersal tends to concentrate seed lots, making them vulnerable to predation if they are deposited in open areas. However, being dispersed by a large vertebrate will ensure long‐distance dispersal, often to areas beyond that which was subject to fire. These would include vegetated areas, where the large seeds could lodge in safe sites and produce seedlings that are able to survive under the shade of established plants. © 2005 The Linnean Society of London, Botanical Journal of the Linnean Society, 2005, 149, 433–449.